Characteristics of Carbon from Oil Palm Shell Activated by Low Concentration of Zinc Chloride Activator - Joko Sulistyo; Purnama Darmadji; Sri Nugroho Marsoem (Wood Research Journal, 2014)
Currently, a large amount of oil palm shell has been dumped as waste from  palm oil processing  in Indonesia.  Using  a low  concentration  of  zinc   chloride  (ZnCl2),  thermal treatment during  pre-carbonization  was applied  in  the  preparation  of activated carbon from  oil palm shells at various temperatures and reaction durations. This study, therefore, aims to investigate the   physical  and chemical  characteristics  of  activated  carbon  prepared.  Oil palm  shells  collected  from   a plantation  in Palembang were carbonized by  two methods, one-stage carbonization (at 300°C for 3 hours) and two-stage carbonization (at 300°C for 3 hours, then  at  600°C for an  hour)  before chemical activation using ZnCl2, at  a concentration of 10  and 15%wt. Activation of oil palm shell charcoal was conducted at  600,  700,  and 800°C and reaction times  of 60,  120,  and 180  minutes. The results showed two-stage carbonization, high  temperature, and prolonged reaction time is bound to increase burn-off as well  as methylene blue adsorption, and decrease the  yield and volatile matter content of  the  activated carbon prepared. Meanwhile, high  ZnCl2  concentration increased the  ash content and the  methylene blue adsorption. In addition, the  two-stage carbonization  had higher iodine  adsorption  compared to the  one-stage  carbonization.  The activated  carbon with  high  iodine (769.3 mg/g) and methylene blue adsorption (133.7 mL/g) levels was obtained by  two-stage carbonization using 15%wt ZnCl2 at a temperature and reaction time of 800°C and 180 minutes, respectively.